HERITABILITAS BOBOT LAHIR SAPI BALI DAN PERSILANGANNYA YANG DIPELIHARA SECARA SEMI-INTENSIF DI KABUPATEN KUPANG (HERITABILITY OF BALI CATLLE BIRTH WEIGHT AND IT’S CROSSBRED UNDER SEMI-INTENSIVE RAISING IN KUPANG DISTRICT) - Agustinus Ridlof Riwu; Johny Nada Kihe (JURNAL NUKLEUS PETERNAKAN, 2015)
Research aimed was to know heritability of Bali cattle and its crossbred. Data was collected by survey and interview to the farmers and observation with measurement on the cattle body linear sizes to predict bulls and cows live weight, calf birth weight is weighted below twenty-hour post partum and was analyzed using regression analysis and continued with heritability calculated. The result from this research is: averages of cow weight were: 262,3980 ± 17,4870 kg; Bali cattle bull weight: 345,1560 ± 14,4004 kg and high quality bull weight: 420,4060 ± 24,1006 kg; birth weight of Bali cattle: 16,0364 ± 0,4892 kg and birth weight of crossing Bali cattle: 26,5312 ± 2,4015 kg. The heritability of Bali cattle birth weight was: 0,0846 is estimated from the regression on mother-offspring regression; 0,0680 estimated from father-offspring regression and 0,0754 is estimated from parent-offspring regression. The heritability off crossing Bali cattle birth weight was: 0,2526 is estimated from the regression on mother-offspring regression; 0,1992 estimated from father-offspring regression and 0,2220 is estimated form parent-offspring regression. The good heritability for crossing Bali cattle birth weight is estimated from the regression of mother-offspring is: 0,2520 with the regression equation was Y = -5,64 + 0,1260 cow weight (kg); 0,0846 for Bali cattle is estimated from the regression of mother-offspring with the regression equation was Y = 4,61 + 0,0423 cow weight (kg). The result from crossbreeding of Bali cattle cows with high quality bulls will be increased birth weight 65,45 percent from Bali cattle birth weight; and the heritability of the birth weight is more depend on the cow’s condition. ABSTRAK Suatu penelitian survey dilakukan untuk mengetahui heritabilitas bobot lahir sapi Bali dan persilangannya, data yang dikumpulkan: bobot induk, pejantan dan berat lahir anak sapi Bali dan persilangannya. Analisa data menggunakan analisis regresi selanjutnya dihitung heritabilitas bobot lahir. Dari penelitian ini diperoleh: bobot induk: 262,3980 ± 17,4998 kg, bobot pejantan lokal: 345,1560 ± 14,4004 kg dan pejantan unggul: 420,4060 ± 24,1006 kg; bobot lahir sapi Bali: 16,0364 ± 0,4892 kg dan bobot lahir sapi Bali hasil persilangan: 26,5312 ± 2,4015 kg; heritabilitas bobot lahir sapi Bali :berdasarkan dugaan regresi anak-induk 0,0846; dugaan regresi-anak-pejantan 0,0680 dan berdasarkan dugaan regresi anak-tetua 0,0754.; heritabilitas bobot lahir sapi Bali hasil persilangan berdasarkan dugaan regresi anak-induk 0,2526, dugaan anak-pejantan 0,1992 dan berdasarkan dugaan regresi anak-tetua 0,2220; heritabilitas bobot lahir tertinggi pada sapi Bali hasil persilangan adalah berdasarkan dugaan regresi anak-induk yakni 0,2520 dengan persamaan regresi Y = -5,64 + 0,1260 bobot induk (kg), dan pada sapi Bali berdasarkan dugaan regresi anak-induk, heritabilitasnya: 0,0846 dengan persamaan regresi Y = 4,61 + 0,0423 bobot induk (kg). Hasil persilangan sapi Bali dengan pejantan unggul meningkatkan bobot lahir sebesar 65,45 persen dari bobot lahir sapi Bali dan heritabilitas atas sifat yang diturunkan (bobot lahir) lebih banyak ditentukan oleh kondisi induk dibandingkan dengan pejantan atau dari tetua (pejantan + induk), baik untuk sapi Bali maupun untuk hasil persilangan sapi Bali.